A SENSITIVE AGAR PLATE ASSAY FOR SCREENING INHIBITORS OF ?-AMYLASE - ASHU RANI; SATISH K SHARMA; AMARJIT NATH (The Bioscan, 2019)
A simple method for estimation of α-amylase inhibitor activity was developed and is being reported for the first time in this paper. This method was used for the qualitative screening of local common bean (Phaseolus vulgaris L.) selections of Kinnaur district for α-amylase inhibitor activity. Amongst seven common bean selections, Triloki cultivar had maximum α-amylase inhibitor activity. The results were authenticated by quantitative estimation involving the quantification of the reducing sugar (maltose equivalent) and similar results were found. Agar plate method involving less expensive chemicals and no sophisticated pieces of equipment can hence be used for screening of a large number of samples for the presence of α-amylase inhibitor. This has an application in testing natural resources for antidiabetic factors.